2021
DOI: 10.3389/fvets.2021.629006
|View full text |Cite
|
Sign up to set email alerts
|

Dose-Effect of Zearalenone on the Localization and Expression of Growth Hormone, Growth Hormone Receptor, and Heat Shock Protein 70 in the Ovaries of Post-weaning Gilts

Abstract: Zearalenone (ZEA) has an estrogen-like effect, which can injure the reproductive system of animals, causing infertility, and abortion in sows. However, the underlying mechanisms are still not clear. The objective of this study was to assess the effects of ZEA on the localization and expression of growth hormone (GH), growth hormone receptor (GHR), and heat shock protein 70 (Hsp70) in the ovaries of post-weaning gilts. Forty healthy post-weaning gilts were randomly provided one of four diets: normal basal diet … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 52 publications
0
8
0
Order By: Relevance
“…During the experimental period, gilts were fed a basal diet (control group) or a ZEA-contaminated diet (the basal diet supplemented with 1.0 mg/kg ZEA). Zearalenone levels used in the present study were based on our previous investigations in Shandong Province of China from 2007 to 2020 and recent literature [ 12 , 52 , 53 , 54 ]. The basal diet ( Table 3 ) used in the present study was prepared according to the NRC (2012) [ 55 ].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…During the experimental period, gilts were fed a basal diet (control group) or a ZEA-contaminated diet (the basal diet supplemented with 1.0 mg/kg ZEA). Zearalenone levels used in the present study were based on our previous investigations in Shandong Province of China from 2007 to 2020 and recent literature [ 12 , 52 , 53 , 54 ]. The basal diet ( Table 3 ) used in the present study was prepared according to the NRC (2012) [ 55 ].…”
Section: Methodsmentioning
confidence: 99%
“…Total RNA was extracted from the ovaries of gilts using RNAiso Plus (Applied TaKaRa, DaLian, China) according to manufacturer’s instructions and the literature of Song et al [ 53 ] and Zhou et al [ 59 ], and the purity and concentration of the RNA were evaluated by Eppendorf Biophotometer (DS-11, Denovix, Wilmington, DE, USA) at an absorbance ratio of 260/280 nm (a range of 1.8~2.0 indicates a pure RNA sample). The RNA integrity was verified by agarose gel electrophoresis.…”
Section: Methodsmentioning
confidence: 99%
“…Gilts were randomly divided into two treatments (10 gilts per treatment) to receive a basal diet or a 1.0-mg/kg dose ZEA diet (basal diet added with 1.0-mg/kg ZEA). The zearalenone dosage used in this current study was due to previous investigations and the recent literature [ 60 , 61 , 62 , 63 ], according to Liu et al [ 28 ], for 35 d following a 7-d adaptation.…”
Section: Methodsmentioning
confidence: 99%
“…For example, ZEA and DON belong to the trichothecene group of mycotoxins [10]. In vivo and in vitro experiments indicated that ZEA and its metabolites exert estrogenic effects, resulting in functional and morphological alterations in ovarian follicles and oocytes, and ZEA is unequivocally implicated in reproductive disorders of swine and other domestic animals [15][16][17]. However, it is unclear whether mycotoxins have dose-dependent effects on the ovarian reserves of gilts.…”
Section: Introductionmentioning
confidence: 99%
“…Compared with a single mycotoxin, multiple mycotoxins contained in naturally moldy feed have more severe toxicity due to their synergism. However, most studies of the effects of mycotoxins on the growth and development of pigs added a purified mycotoxin to the diet [13,16,[21][22][23], and the hygiene standards in China and the EU for porcine diets were established according to results based on experiments conducted with purified mycotoxin. To date, the dose-dependent effects of including different levels of mycotoxin-contaminated cereal grains on the growth performance and ovarian follicle reserve in replacement gilts is poorly understood.…”
Section: Introductionmentioning
confidence: 99%